Characteristic properties of the microstructure and microtexture of medium-carbon steel subjected to sulfide stress cracking - Andrey V. Malinin; Vil D. Sitdikov; Valeria E. Tkacheva; Artem K. Makatrov; Ilya V. Valekzhanin; Andrey N. Markin (Frontier Materials & Technologies, 2023)
Increasing the resistance of steel products to sulfide stress cracking (SSC) is one of the topical issues of the oil and gas industry. Among various factors determining the SSC resistance of a material is the structure-phase state of the material itself and the crystallographic texture associated with it. This paper analyzes these features using the scanning electron microscopy (SEM), transmission electron microscopy (TEM), and microroentgen electron backscattered diffraction (EBSD) techniques. As the research material, a production string (PS) coupling made of medium-carbon steel was selected, which collapsed by the mechanism of hydrogen embrittlement and subsequent SSC. For the first time, by the SEM method, using the location and mutual orientation of cementite (Fe3C) particles, at high magnifications, the authors demonstrated the possibilities of identifying the components of upper bainite, lower bainite, and tempered martensite in steels. The presence of the detected structural components of steel was confirmed by transmission electron microscopy (TEM). Using the EBSD method, the detailed studies of microtexture were conducted to identify the type and nature of the microcrack propagation. It is established that the processes of hydrogen embrittlement and subsequent SSC lead to the formation of {101} <0 0>, {100} <001>, {122} <2 0>, {013} <211>, {111} < 00>, {133} < 1>, {3 } <201> grain orientations. It is shown that the strengthening of orientations of {001} <110>, {100} <001>, {112} <111>, and {133} < 1> types worsens the SSC resistance of the material. Using the EBSD analysis method, the influence of coincident site lattice (CSL) grain boundaries on the nature of microcrack propagation is estimated. It is found that the Σ 3 CSL grain boundaries between the {122} <2 0> and {111} < 00>, {012} < 0>, {100} <001> plates of the upper bainite inhibit the microcrack development, and the Σ 13b, Σ 29a, and Σ 39a CSL grain boundaries, contribute to the accelerated propagation of microcracks. For comparative analysis, similar studies were carried out in an unbroken (original) coupling before operation.